Experimental work using Microsoft Hololens 2 to improve mental workload and task performance - Abdul Rani, Nadia; Che Muslim, Muhammad Aiman; Abdul Aziz, Faieza (ModTech Publishing House, 2024)
The potential of Augmented Reality (AR) and Mixed Reality (MR) applications to enhance learning and comprehension of complex laboratory procedures is being explored in this study. The research investigates the effectiveness of MR and AR applications in conducting experiments on electro-pneumatic systems and assesses the cognitive workload involved. The experiment utilized Microsoft HoloLens 2 and tablets for the electro-pneumatic component. Participants were divided into three groups (A, B, and C) with 30 participants in each group to conduct paper-based instruction experiments, AR experiments, and MR experiments. The NASA Task Load Index was employed to evaluate the performance and effectiveness of MR and AR applications in the electro-pneumatic system experiments. The results indicated that 70% of participants preferred MR over AR due to its provision of clearer instructions with holographic guidelines. Furthermore, the interpretation of the NASA-Task Load Index (NASA-TLX) scores revealed that MR-based applications exhibited the lowest mean mental workload value compared to AR applications.